System change in practice: A report from the EHC Think Tank workstreams on Access Equity and Future Care Pathways - Gacser Zita; Bourke Steven; Hosszú Dalma; Daniels Susan (The Journal of Haemophilia Practice)
The European Haemophilia Consortium (EHC) Think Tank was established as a platform for system change to ensure the healthcare ecosystem remains effective and relevant for people with bleeding disorders and other rare diseases. Operating alongside traditional advocacy initiatives, it comprised a series of thematic workstreams in which multiple stakeholders explored and co-designed potential solutions for specific aspects of the healthcare system. This final report from the workstreams on Access Equity and Future Care Pathways summarises recommendations for system change and the actions needed to achieve critical goals.